Exploring Digital Forensics: A Decade of Law-Related Journal Articles (2012-2022) - Widya Visa, Hikmah Tara; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This study meticulously examines the intersection of Digital Forensic and Image Processing, utilizing a targeted appIn this data article, we conducted a comprehensive search on Lens.org, utilizing keyword-based queries for 'Digital Forensic' and 'Image Processing' to identify a total of 10,822 documents. We refined our search by applying filters, specifically targeting 'Journal Articles' resulting in 7,258 documents, and then further narrowed the scope to the past decade (2012-2022), yielding 5,674 relevant documents. Finally, we focused on the subject matter 'Law,' which led to 403 documents. The data collected serves as a valuable resource for researchers and authors in the field of digital forensics, enabling easier access to a wealth of literature on the subject. This dataset facilitates in-depth investigations and offers insights into the intersections of digital forensics and image processing, benefiting researchers worldwide.roach via Lens.org. Employing keywords "Digital Forensic" and "Image Processing," a substantial dataset of journal articles spanning a decade (2012-2022) was curated, focusing on the legal aspects. Through precise filtering processes, documents falling under the category of "Journal Articles" and related to "Law" were extracted and exported in CSV and BIBTEX formats. The objective was to amalgamate the realms of digital forensic investigations and image processing techniques. Our analysis illuminates significant advancements and methodologies utilized in enhancing digital forensic practices, particularly concerning image analysis and interpretation. This research not only enriches the existing academic discourse but also offers practical implications for forensic professionals, enabling them to leverage cutting-edge image processing technologies for more precise and insightful digital forensic investigations. Highlights : Extensive Data Collection: Over 10,000 documents retrieved. Recent Decade Focus: Articles from 2012-2022. Legal Context: Emphasizing relevance to law-related research. Keywords:Digital Forensics, Image Processing, Law, Journal Articles, Research Resource.